1997
DOI: 10.1046/j.1365-2036.1997.133311000.x
|View full text |Cite
|
Sign up to set email alerts
|

Double‐blind study of the effect of cisapride on constipation and abdominal discomfort as components of the irritable bowel syndrome

Abstract: SUMMARYAim : To study the effect of prokinetic treatment with cisapride in patients with constipation-predominant irritable bowel syndrome. Patients and methods : Ninety-six patients were randomly assigned to treatment with either cisapride 5 mg three times daily or placebo three times daily for a period of 12 weeks. The dosage could be doubled after 4 weeks. Presence of the target symptoms abdominal pain, constipation and abdominal bloating was an obligatory criterion for inclusion in the study. Results : Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 0 publications
0
43
1
Order By: Relevance
“…There are two double-blind trials with 5-10 mg of cisapride on IBS [24,25]. No significant differences were found between placebo and cisapride, with the exception of stool passage (which improved with the drug) in one of the trials [25]. These results limit cisapride use in IBS to patients with remarkable functional symptomatology of the upper gastrointestinal tract.…”
Section: Prokinetic Drugsmentioning
confidence: 94%
See 1 more Smart Citation
“…There are two double-blind trials with 5-10 mg of cisapride on IBS [24,25]. No significant differences were found between placebo and cisapride, with the exception of stool passage (which improved with the drug) in one of the trials [25]. These results limit cisapride use in IBS to patients with remarkable functional symptomatology of the upper gastrointestinal tract.…”
Section: Prokinetic Drugsmentioning
confidence: 94%
“…Cisapride is a benzamide derivative with cholinergic activity in the myoenteric plexus through serotonin-mediated effects (5-HT 4 agonism). There are two double-blind trials with 5-10 mg of cisapride on IBS [24,25]. No significant differences were found between placebo and cisapride, with the exception of stool passage (which improved with the drug) in one of the trials [25].…”
Section: Prokinetic Drugsmentioning
confidence: 99%
“…hances gastrointestinal motor function and may improve the difficulty of stool passage in constipation-predomi-Thus, loxiglumide did not beneficially affect any of the gastrointestinal symptoms of IBS [69]. Similarly, the nant IBS patients but has little or no effect on the overall symptoms of constipation and abdominal discomfort CCK-B receptor antagonist CI-988 did not improve the symptoms of IBS in patients with generalised anxiety [62]. In diarrhoea-predominant IBS patients, cisapride may increase the occurrence of abdominal pain [63], per-disorder, but tended to exacerbate the diarrhoea [70].…”
Section: Inhibition Of Afferent Nerve Activitymentioning
confidence: 99%
“…Two other high-quality trials, however, showed that cisapride was not superior to placebo in the treatment of constipation and abdominal discomfort in IBS [96,97]. It has a role as a promotility agent in the upper gastrointestinal tract.…”
Section: Constipation-predominant Ibsmentioning
confidence: 99%